Pemanfaatan Polybag Hijau dalam Optimalisasi Pekarangan untuk Mendukung Kemandirian Pangan Keluarga di Desa Sadawarna - Lizza Fauziah Suroya; Laras Sirly Safitri; Desy Triastuti; Wiwik Endah Rahayu; Enceng Sobari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Family food security and self-sufficiency are important pillars in building national security. Until now, yard space has not been utilized to become productive and beautiful land, while the potential of yard space in Sadawarna Village to achieve family food self-sufficiency is quite high. The objective of this community service program is to optimize backyard land in Sadawarna Village using green polybags as an effort to achieve food self-sufficiency. The methods employed in this activity include agricultural extension through group-based approaches such as socialization, demonstrations of techniques, trials, and discussions. Open discussions were then conducted so that participants could ask questions, share experiences, and discuss the challenges they faced. Optimizing backyard land with green polybags effectively increased the understanding and interest of the Women Farmers Group (KWT), as indicated by an average post-test score increase of 1.46 points from the pre-test as an indicator of the success of knowledge transfer and technology adoption.